2016
DOI: 10.1155/2016/6713807
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Dermatosis in an End-Stage Renal Disease Patient: A Case Report and Literature Review

Abstract: Patients with advanced chronic kidney disease including ESRD patients may present with a wide spectrum of cutaneous abnormalities, ranging from xerosis to hyperpigmentation to severe deforming necrotizing lesions. Skin problems are not uncommon in this population of patients, with a clinical presentation that can be quite bizarre, mandating a long list of differential diagnostic possibilities, and subsequent rise of a puzzling diagnostic challenge. We describe an ESRD patient who presented with blistering, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, specific studies on the use of dapsone in patients with concurrent ESKD and pemphigoid diseases are limited. This kind of treatment was reported in eight cases and benefited four patients with an average reported dose of 62.5 mg/day ( 20 , 72 , 74 , 75 ). Adverse effects including epigastric pain and mild hypertension were reported ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, specific studies on the use of dapsone in patients with concurrent ESKD and pemphigoid diseases are limited. This kind of treatment was reported in eight cases and benefited four patients with an average reported dose of 62.5 mg/day ( 20 , 72 , 74 , 75 ). Adverse effects including epigastric pain and mild hypertension were reported ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical course. BPDAI: bullous pemphigoid disease area index therefore, it was necessary to carefully differentiate the diagnosis when we observed bullous dermatosis (10). Although there are limited data on the incidence of BP in ESKD patients, one single-center 10-year study showed that the incidence of BP in peritoneal dialysis patients was 3/478.3 person-years (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited data on the incidence of BP in ESKD patients, one single-center 10-year study showed that the incidence of BP in peritoneal dialysis patients was 3/478.3 person-years (7). As a rare autoimmune dermopathy, IgArelated diseases, such as linear IgA dermatosis and dermatitis herpetiformis, have been reported in ESKD patients, being characterized by subepidermal vesicles with IgA deposition in the dermal papillae and BMZ (10).…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that xerosis could be linked to anuria [5] The prevalence of xerosis in ESRD patients has been reported significantly in the above studies and is about 63% to 96%. [5][6][7][8][9][10][11][12]Various ways to control this disorder have been suggested, one of which is to reduce the duration of skin-to-skin contact with water. It has also been suggested to use superficial skin moisturizers in these patients.…”
Section: Superficial Skin Infection That Can Be Bacterial Fungal or Viralmentioning
confidence: 99%